Odontocetes of the Southern Ocean Sanctuary - Van Waerebeek, Koen; Leaper, Russell; Baker , Alan N.; Papastavrou, Vassili; Thiele, Deborah; Findlay, Ken; Donovan, Greg; Ensor, Paul (J. Cetacean Res. Manage., 2023)
Twenty-eight odontocete species were identified as occupying sub-Antarctic and Antarctic habitat covered by the 1994 IWC-established Southern Ocean Sanctuary. Toothed whales evidently play an important part in the Antarctic polar ecosystem. Twenty-two species are autochthonous in showing a regular, apparently year-round, presence in the Sanctuary: Physeter macrocephalus, Kogia breviceps, Orcinus orca, Globicephala melas edwardii, Pseudorca crassidens, Lagenorhynchus cruciger, Lagenorhynchus obscurus, Lissodelphis peronii, Cephalorhynchus commersonii, Cephalorhynchus hectori, Tursiops truncatus, Delphinus delphis, Phocoena dioptrica, Hyperoodon planifrons, Berardius arnuxii, Ziphius cavirostris, Tasmacetus shepherdi, Mesoplodon layardii, Mesoplodon traversii, Mesoplodon grayi, Mesoplodon bowdoini and Mesoplodon hectori. Six species are considered vagrants into the Sanctuary: Kogia sima, Grampus griseus, Steno bredanensis, Mesoplodon peruvianus, Mesoplodon densirostris and Mesoplodon mirus. However, vagrant status of these three mesoplodonts is only provisionally assigned, considering that improved knowledge of diagnostic features of beaked whales should, as in recent years, continue to facilitate at-sea identification. Two species are considered as having a ‘contiguous’ range (records less than 2° north of Sanctuary boundaries): Mesoplodon ginkgodens (at 39°S) and Mesoplodon mirus (at 38°24’S). The habitual southern range of at least four odontocetes extends significantly farther poleward than expected. G. melas edwardii is regularly encountered south of the Antarctic Polar Front, much like M. grayi which is known to reach the Ross Sea ice edge (ca. 67°S). Z. cavirostris and L. obscurus cross the Polar Front occasionally. The distribution of M. peruvianus and M. traversii and their relation to SST are unclear. Their southernmost records, 42°31’S and 44°17’S respectively, may either be extralimital or, more likely, reflect ordinary austral range. Temporally non-aligned distribution patterns of Hyperoodon planifrons in Antarctic and South African waters may suggest stock segregation.